Transforming Islamic Education Through Maslahah Mursalah Perspective: Innovation of Islamic Religious Education Books with Disaster Awareness to Enhance Madrasah Resilience - Imam Karya Bakti; Zulkarnain; Auwalu Shuaibu Muhammad; Kusaeri (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
The approach of disaster mitigation in Islamic religious education urgently needed to be adopted due to the high frequency of disaster occurrences and their impact on madrasahs, particularly in disaster-prone areas. The lack of literature and practical guidelines on disaster mitigation education is one of the main obstacles that reduces madrasah's involvement in disaster risk reduction efforts. This study aims to identify the concept of Islamic education transformation in disaster awareness and the form of innovation in Islamic religious education textbooks based on the perspective of Maslahah Mursalah. Utilizing a Systematic Literature Review (SLR) approach, the research findings highlight: (1) The concept of Islamic education transformation in disaster awareness from the perspective of Maslahah Mursalah focuses on three levels of maslahah: (a) al-Maslahah al-Dharuriyat, where education emphasizes a deep understanding of Islamic teachings related to self-protection and social responsibility in disaster situations, (b) al-Maslahah al-Hajiyat, ensuring the availability of facilities and environments that support effective learning related to disasters, (c) al-Maslahah al-Tahsiniyat, education emphasizes the formation of student character with values such as mutual assistance, cooperation, and empathy in facing disasters. (2) The innovation of Islamic religious education textbooks based on disaster with the perspective of Maslahah Mursalah includes the incorporation of Islamic laws related to disasters into the curriculum with an emphasis on relevance and flexibility, emphasizing the relevance and flexibility of the curriculum, using case studies from Islamic history, and providing practical resources such as evacuation guides in preparing students to face disasters. This research contributes to understanding and implementing disaster risk reduction policies in Islamic religious education, the development of interdisciplinary-based disaster textbooks, and the study of Islamic education materials with the perspective of disaster mitigation based on Maslahah Mursalah.